THE EFFECT OF PROBLEM-BASED LEARNING AND DISCOVERY LEARNING MODELS ON STUDENTS' FINANCIAL ACCOUNTING LEARNING OUTCOMES AT PUBLIC VOCATIONAL HIGH SCHOOL 1 KENDARI SOUTHEAST SULAWESI - Rahmiatin, Sitti; Susanti, Santi; Sumiati, Ati (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
This stdy aimed to investigate how models of problem based learning and discovery learning affected financial accounting leanring results of SMK Negeri 1 Kendari, Southeast Sulawesi Province. Using a post-test only control group design and an experimental strategy as the study technique. With a simple randomized sampling approach, this research included Class XI students majoring in Institutional Financial Accounting (AKL) at SMK Negeri 1 Kendari, resulting in a sample of Class XI1 and XI3 totaling 68 individuals. This research used the Kolmogrov-Smirnov test as the normality test; the homogeneity test was done with the variance test (f-test); the hypothesis test was done with the t-test. Whether H0: µ1 = µ2 indicates that there is no effect of the problem-based learning and discovery learning models on learning outcomes or H1: µ1 > µ2 indicates that the models have an impact on students's learning outcomes related to financial accounting, so guiding the generation of a hypothesis based on the test that will be conducted.